Public Participation as a Constitutional Right in the Process of Preparing Environmental Documents: Partisipasi Publik sebagai Hak Konstitusional dalam Proses Penyusunan Dokumen Lingkungan - Achmad Muchsin (Jurnal Konstitusi, 2024)
This study aims to explore the legal concerns associated with limitations on public involvement in the preparation of environmental documentation under the Job Creation Law. This research is doctrinal and conducted using statutory, conceptual, and philosophical approaches. The results of the research and analysis conclude that public participation is a constitutional right. Therefore, limiting public participation, particularly for individuals who are directly impacted by a proposed business plan and/or activity, constitutes a constitutional violation. Restrictions on participation can potentially create antinomies or conflicts of norms between articles or even regulations within a law. Furthermore, in a broader scope, restrictions on public participation conflict with the principles of international environmental law, especially procedural environmental law.